INTERKONEKSITAS FEMINISME MUSLIM DAN GERAKAN PEMBAHARUAN DI TIMUR TENGAH - Chakim, Sulkhan (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2010)
This paper discusses the interconnection of feminism and the reform movement in the Muslim Middle East. Target to beobtained, and parse the convergence and tension between Muslim feminist movement with the movement of Islamic reform. Intersectionbetween the two species include the idea of Islamic unity, the question of religious issues, political interests and representation of interests ofeach of them different.